Strategy of Community Pro-Environmental Behavior for Sustainable Development - Hanna Cintya Maulidiana; Wike Wike; Sumi Lestari; Dini Atikawati (Postgraduate, University of Mataram, 2023)
This research aims to develop pro-environmental behavior strategies of community in sustainable development. This research is qualitative research, which emphasized on understanding certain phenomena in depth, explained descriptively in order to explain the description of people's pro-environmental behavior according to conditions in the field objectively and comprehensively. The research was conducted in October 2023, located in Turigede Village, Kepohbaru District, Bojonegoro Regency. The results of this research indicate that Turigede Village Community has carried out several aspects of pro-environmental behavior in the form of saving electrical energy, mobility and transportation, collecting rubbish that could be resold, as well as being enthusiastic about participating in community service. Government and the environmental conditions of the village still have many wild bushes and bamboo forests. Meanwhile, the supporting factors for community pro-environmental behavior are cognitive factors in the form of community knowledge. It explains how to care for the environment and situational factors consisting of villages having various institutions whose functions can be optimized